Driving industrial growth through MSMEs: Towards an India’s vision of a 5 trillion economy - Hannan, Abdul; Raj, Shubham; Kumari, Vandana; Fatma, Ramla; Alam, Imran (The International tax journal, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are fundamental to India's industrial sector, facilitating inclusive growth, creating employment, and advancing regional development. This study utilises secondary data from the Reserve Bank of India (RBI) and the Ministry of MSME to emphasise their contributions to GDP, manufacturing, exports, and employment—representing approximately 30% of GDP, over 45% of manufacturing output, nearly 43% of exports, and sustaining livelihoods for more than 111 million individuals. Their robust existence, especially as microenterprises in rural and semi-urban regions, guarantees economic inclusion and social stability. Nevertheless, the industry persists in encountering substantial obstacles, such as a ₹20–25 lakh crore credit deficit, restricted access to formal financing for micro enterprises, low productivity, inadequate technological adoption, inefficiencies in scale, delayed payments, and insufficient integration into global supply chains. The study emphasises the necessity for specific policy interventions to address these constraints, including cash-flow-based funding, technological advancement, cluster growth, rigorous enforcement of timely payments, and a streamlined facilitation system. Enhancing the MSME ecosystem is crucial for expediting industrial growth and achieving regional equilibrium, as well as for fulfilling India's aspiration of a 5 trillion economy.